2013
DOI: 10.1016/j.celrep.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Local Functional Overconnectivity in Posterior Brain Regions Is Associated with Symptom Severity in Autism Spectrum Disorders

Abstract: Summary While growing evidence indicates atypical long-distance connectivity in autism spectrum disorders (ASD), much less is known about local connectivity, despite conjectures that local overconnectivity may be causally involved in the disorder. Using functional connectivity MRI and graph theory, we found that local functional connectivity was atypically increased in adolescents with ASD in temporo-occipital regions bilaterally. Posterior overconnectivity was found to be associated with higher ASD symptom se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
178
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(222 citation statements)
references
References 45 publications
(57 reference statements)
40
178
3
1
Order By: Relevance
“…They are in line with earlier results of population-based studies on adolescents and adults, indicating that RS connectivity correlates with both autistic traits [49][50][51][52] and ASD symptom severity scores in clinical samples. 14,53,54 However, our results extend the latter findings as they show the relationship within twin pairs, where most genetic and environmental confounders are controlled for. Indeed, twins with higher autistic traits showed increased within-SN connectivity compared to their co-twins.…”
Section: Discussioncontrasting
confidence: 39%
“…They are in line with earlier results of population-based studies on adolescents and adults, indicating that RS connectivity correlates with both autistic traits [49][50][51][52] and ASD symptom severity scores in clinical samples. 14,53,54 However, our results extend the latter findings as they show the relationship within twin pairs, where most genetic and environmental confounders are controlled for. Indeed, twins with higher autistic traits showed increased within-SN connectivity compared to their co-twins.…”
Section: Discussioncontrasting
confidence: 39%
“…More recent fMRI studies using connectivity measures derived from resting state measures report both under- (Dinstein et al, 2011) and over-connectivity (Keown et al, 2013;Supekar et al, 2013) or normal patterns (Tyszka et al, 2014). However, a recent article by (Hahamy et al, 2015) suggested that there are marked individual differences (or idiosyncrasies) shown by whole-brain analyses of connectivity, with ASD participants showing substantially more deviation from group-averaged patterns of inter-hemispheric connectivity.…”
Section: Aberrant Cortical Connectivity In Asdmentioning
confidence: 97%
“…Reports have been published revealing reduced long-range, distant brain connectivity during both task-specific (Besag 2004;Koshino et al 2005Koshino et al , 2008Kana et al 2006;Just et al 2007) and restingstate paradigms Weng et al 2010). Likewise, a number of studies have shown reduced short-range, local connectivity (Besag 2004;Koshino et al 2005Koshino et al , 2008Just et al 2007;Kana et al 2011). Results from yet other studies have shown increased connectivity, both long range (Ben Bashat et al 2007;Cheng et al 2010;Supekar et al 2013) and short range (Weng et al 2010;Anderson et al 2011;Keown et al 2013;Khan et al 2013;Lewis et al 2013). …”
Section: Aberrant Connectivity In Autismmentioning
confidence: 97%